Development of Muhammadiyah in Ciledug Tangerang: Between Challenges and Achievements 1958-2012 - Muhammad Aufa Akmal; Kurniawati; Nurzengky Ibrahim; Pamela Ayesma (Pusat Pengkajian dan Pengembangan Islam Jakarta (PPIJ), 2025)
This article aims to reveal the beginning of Muhammadiyah's entry in Ciledug, Tangerang City, and its development in the lives of the Ciledug community from 1985 to 2012, as well as the challenges faced and Muhammadiyah's contribution to the welfare of the community in Ciledug, Tangerang. This study uses a qualitative method with a descriptive approach. Respondents in this study were Muhammadiyah figures in Ciledug, leaders of Muhammadiyah institutions, and the community. The results of this study reveal that Muhammadiyah entered the Ciledug Tangerang area around 1958. There are challenges and achievements in the development of Muhammadiyah in Ciledug, Tangerang. The challenges faced by Muhammadiyah in Ciledug, Tangerang are community rejection, such as the prohibition of religious studies, sabotage during the construction of mosques, and the prohibition of schools for children of Muhammadiyah members. The achievements that Muhammadiyah has successfully achieved in Ciledug, Tangerang are contributions through charitable efforts in the fields of da'wah, education, social, and health. Thus, it can be concluded that the difficulties faced by Muhammadiyah in spreading its influence in the Ciledug, Tangerang community did not actually make Muhammadiyah back down from spreading its influence in the Ciledug, Tangerang community. Instead, Muhammadiyah continued to strive to improve the welfare of the community in Ciledug, Tangerang, through charitable activities. Therefore, as it developed, Muhammadiyah was well-received by all levels of Ciledug, Tangerang society. Muhammadiyah then developed into a large organization that continues to this day.